Theobroma cacao, a new host for Brevipalpus yothersi (Acari: Tenuipalpidae) in Peru - Alonso Escobar-Garcia, Hector; Andrade, Daniel Junior de [UNESP]; Carrillo, Daniel; Ochoa, Ronald (Acarologia-universite Paul Valery, 2021)
Brevipalpus yothersi Baker (Acari: Tenuipalpidae) is reported for the first time on cocoa, Theobroma cacao L. (Malvaceae) in northwestern Peru. Mites were collected from organic cocoa smallholdings from September to December 2020 in eight localities (three Provinces) of the Piura Department. The highest mite population density was found on peduncle and epicarps of fruits of different phenological stages, and the lowest density on the leaves.
Keywords: Acarofauna; cocoa beans; emerging pest; flat mites; Tetranychoidea